2008
DOI: 10.1002/asl.169
|View full text |Cite
|
Sign up to set email alerts
|

Forecast impact experiment with a constellation of GPS radio occultation receivers

Abstract: A forecast impact experiment with a constellation of global positioning system radio occultation (GPSRO) receivers is presented. The constellation includes the six COSMIC/FORMO-SAT-3 satellites, combined with the GRACE-A and CHAMP satellites. It is shown that rising and setting occultations measured with the COSMIC satellites have similar bending angle error characteristics. The GPSRO measurements improve the root mean square (rms) geopotential height forecast errors at 500, 200, and 100 hPa in both the Northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 19 publications
2
56
0
Order By: Relevance
“…Not only do they contribute independent information that is complementary to other satellite and in-situ observations, their essential lack of bias actually improves the impact of other sensors that have biases (Healy, 2008).…”
Section: Numerical Weather Analysis and Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only do they contribute independent information that is complementary to other satellite and in-situ observations, their essential lack of bias actually improves the impact of other sensors that have biases (Healy, 2008).…”
Section: Numerical Weather Analysis and Predictionmentioning
confidence: 99%
“…Figure 27 shows that on 12 December a long-standing bias in 100-mb temperatures in the Southern Hemisphere was immediately reduced to near zero by the bias-free RO observations. Figure 28 shows the impact of COSMIC data on NCEP (Cucurull, 2010) and ECMWF (Healy, 2008) forecasts. At NCEP, the anomaly correlation for the forecast 500-mb height shows an eight-hour gain in forecast accuracy at Day 4.…”
Section: Numerical Weather Analysis and Predictionmentioning
confidence: 99%
“…During the last few years, RO measurements have been increasingly used by weather centers around the globe, and they show a surprisingly large positive impact on the quality of atmospheric analyses (Cardinali, 2009), partly due to the fact that they are the only satellite data (so far) that can be assimilated without bias correction (Healy, 2008).…”
mentioning
confidence: 99%
“…In past decades, numerous studies have demonstrated the unique strengths of GPS RO, which include high accuracy and vertical resolution, global coverage, all-weather capability, and self-calibration aptitude (e.g., Kursinski et al, 1997;Hajj et al, 2002;Wickert et al, 2004;Kuo et al, 2004). The data are accepted as an operationally reliable source of information by NWP centers worldwide (Poli et al, 2010), and have shown clear positive impacts on weather forecasting (e.g., Healy, 2008;Buontempo et al, 2008;Cucurull and Derber, 2008;Aparicio et al, 2009;Rennie, 2010) and merits in atmospheric reanalysis projects (Saha et al, 2010;Dee et al, 2011). In particular, RO data are assimilated without any bias correction.…”
Section: Introductionmentioning
confidence: 99%